The Influence of Husband's Assistance Using Audio Visual Methods on Family Planning Participation in Long-Term Contraceptive Methods in Women of Childbearing Age in Kutuk Village, Undaan District, Kudus Regency - Liana Indah Sari; Juda Julia Kristiarini; Yuni Kusmiyati (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Introduction: The population in Indonesia has reached 278.69 million people in July 2023. This figure is up 1.05% from 2022, namely 275.77 million people. To control population growth, the government has created programs, one of which is the long-term contraceptive method family planning program or Long Term Contraceptive Methods in the form of IUDs, Implants, MOW and MOP through the assistance of husbands using audiovisual media. Objectives: Analyzing the Influence of Husband's Assistance Using Audio Visual Methods on Family Planning Participation in Long-Term Contraceptive Methods in Women of Childbearing Age. Methods: This research is quantitative using a quasi experimental study method with control group design. The sample used 15 respondents in the intervention group using audio-visual and 15 respondents in the control group using leaflets. Data analysis used the Paired Sample T-test statistical test, the independent T-test, namely the paired T-test, using the Wilcoxon Test. Results: The participation of women of childbearing age in family planning using long-term contraceptive methods in the intervention group and control group before being given treatment, no one used MKJP family planning (0%) and after being given treatment, the intervention group used MKJP family planning, numbering 6 people (40%) and the control group 2 people (13.3%). Based on the Significant Difference Test using the Mann-Whitney test, the category of husband's knowledge and support for MKJP family planning participation above can be seen as a p-value of 0.000, which means there is a significant difference between before giving the intervention and after giving the intervention. With the results of this test, the data Ho is rejected and Ha is accepted, which means that the use of the audio-visual method influences the level of knowledge which influences the husband's support for family planning for long-term contraceptive methods. Conclusions: The use of audio-visual methods affects the level of knowledge which influences husband's support which causes an increase in family planning participation in long-term contraceptive methods.